Ketersediaan Nitrogen pada Ultisol dengan Aplikasi Kotoran Walet dan Arang Kayu - Nur Indah Wulansari; Akhmad Rizalli Saidy; Bambang Joko Priatmadi (Acta Solum, 2024)
The application of organic matter with a high nitrogen (N) content in combination with the application of wood charcoal is a common soil fertility management practice in Ultisols. This study aims to determine the availability of N in Ultisols, which are applied to swallow droppings and wood charcoal. The experimental design used was a two-factor Completely Randomized Design (CRD), with the first factor being swallow droppings (0.5 and 10 t ha−1) and the second factor being wood charcoal (0, 10, and 20 t ha−1), with as many as three repetitions. As much as 200 g of soil was put into the incubation site, then swallow droppings and wood charcoal were added according to the treatment, stirred until evenly distributed, and then incubated at 70% field capacity for 14 days. The contents of NH4+, NO3-, and pH were observed at the end of the incubation period. The results showed that the application of swallow droppings and wood charcoal increased the content of NH4+, NO3-, and mineral N but lowered soil pH. The best treatment was given to swallow manure at 10 t ha-1 which increased mineral N by 59%, and a combination of swallow manure 10 t ha-1+10 t ha-1 wood charcoal which increased nitrate content by 1,666%. The results of this study indicate that the application of swallow droppings combined with wood charcoal can increase the availability of N in Ultisols.